Generalized additive models (GAMs) approach in modeling rainfall data over Johor area - Suhaimi, N. H. (American Institute of Physics Inc., 2016)
Observations of rainfall data are always changing over time. With the concern over climate change, this study is done to demonstrate how Generalized Additive Models (GAMs) could be utilized to model daily rainfall amount over Johor area. Hence, in modeling rainfall amount, Cyclic Cubic Spline is used as the smoothing technique. This research concentrated on the daily rainfall series with the duration period of 1980 to 2011 from six rainfall stations in Johor area. The results indicated that the rainfall stations demonstrate different behaviours of rainfall patterns. Based on the resulting curves with fitted smoothing parameters, a summary of statistics of the six stations were obtained. The results from the model will then be used to compare the rainfall patterns among the stations.